Correction: Corrigendum: Earliest signs of life on land preserved in ca. 3.5 Ga hot spring deposits - Tara Djokic (Nature Portfolio, 2017)
Nature Communications 8: Article number: 15263 (2017); Published: 9 May 2017; Updated: 16 August 2017. The original manuscript presented evidence that the deposits studied were fluvial rather than marine to support the conclusion that evidence of life on land had been discovered in the 3.4 Ga Dresser Formation, Pilbara Craton, Australia.